(untitled) - Borowick, Jerome N. (Englewood Cliffs, N.J., 1996)
This functional book readies readers for employment as a practicing technical professional by empowering them with effective, proven communication skills. It prepares readers with meaningful lessons on the protocol, sense of audience, and importance of understanding the overall purpose of the technical documentation process. Provides a sound understanding of the elements of various types of engineering documents, scientific documents, and oral presentations. Covers areas such as ethics, responsibility, and establishing credibility. For those interested in technical, occupational, and/or report writing. --This text refers to an out of print or unavailable edition of this title.
Keywords: Technical writing,Communication of technical information,Kỹ thuật bằng văn bản,Thông tin kỹ thuật truyền thông